Modulation of neuropeptide growth factor signalling by anti-cancer substance-P analogues - Tufail-Hanif, Uzma (The University of Edinburgh, 2006)
Widespread metastases are characteristic of the most aggressive form of lung cancer, small cell lung cancer (SCLC). Although initially sensitive to treatment by radio- and chemotherapy, SCLC develops chemoresistance so the 2-year survival rate remains less than 5%. The aberrant proliferation of SCLC is sustained by multiple autocrine and paracrine growth loops involving calcium mobilising neuropeptides such as vasopressin (AVP) and gastrin releasing peptide (GRP). The expression of these neuropeptides and their receptors are a hallmark of the disease and present an important target for therapeutic intervention. Analogues of substance-P, including [D-ArgI,D-Phe5,D-Trp7-9,Leu11]-substance-P (SP-D) and [Arg6,D-Trp7-9,NmePhe8]-substance-P (6-11) (SP-G), are novel anti-cancer agents which inhibit the growth of SCLC cells. Investigations into the mechanism of action of substance- P analogues on bombesin receptors revealed that in addition to blocking bombesin-induced mitogenesis and signal transduction they also have agonist activity. This unique pharmacological activity of 'biased agonism' may be centred to the growth inhibitory effects of these agents.

The aim of this study was to determine whether these agents exhibit 'biased agonist' activity at receptors other than the bombesin/GRP receptor and investigate factors influencing their ability to modulate neuropeptide signalling. Model cell systems consisting of CHO-K1 cell-lines stably expressing GRP or Via receptors were therefore established and the effect of SP-D and SP-G tested. Expression of GRP and Via receptors led to the development of a transformed phenotype as cells showed increased cloning efficiency and survival in soft-agar and suspension growth respectively. GRP and Via receptor expressing cells were less adherent, more migratory and not contact inhibited. Neuropeptide receptor stimulation provided some protection from the cytotoxic effects of etoposide suggesting a role in chemoresistance. Substance-P analogues inhibited normal and anchorageindependent growth of receptor expressing cells. In receptor binding studies on GRP and Via receptor expressing cells, analogue inhibited radioligand binding noncompetitively. Transfected GRP and Via receptors effectively coupled to Ga.q to increase intracellular calcium and the analogues were effective antagonists of this response. Neuropeptide and analogues stimulated ERK activity in GRP and Via receptor expressing cells. Activation of ERK by neuropeptide was rapid and transient while analogue induced activation was delayed and sustained. Analoguestimulated ERK activity was pertussis toxin sensitive whereas neuropeptidestimulated ERK activation was not. In addition, analogue induced ERK activity was blocked by inhibition of EGF receptor kinase. This indicates that SP-D and SP-G facilitate receptor coupling to G-protein Gj/Gq subunits for subsequent calciumindependent ERK activation via EGFR transactivation. Stable cell-lines expressing different levels of Via receptor were used to examine the effect of altering the ratio of receptor to G-protein on the ability of the analogues to direct receptor signalling. There appeared to be little receptor reserve for calcium and ERK responses stimulated by neuropeptide as the efficacy of the response increased with increasing receptor numbers. In contrast, analogue-induced ERK activation occurred with a higher receptor reserve for activated Gj as the magnitude of the response did not increase between medium and high expressing cells. Chimeric Via receptors containing the second (Vjj2) or third intracellular (Vii3) loop of the V2 receptor were used to investigate the influence of substance-P analogues on G-protein selectivity. Both receptors were still capable of binding AVP and SP-G but had altered ability to activate PLC and ERK. The second intracellular loop of VIAR was essential for AVP-stimulated PLC and ERK activation but not for SP-G-induced ERK activation. This confirms that the effects of the agents cause an alteration in the receptor-Gprotein coupling domains of receptors. These findings demonstrate that substance-P analogues are biased agonists of receptors other than GRP receptors, activating downstream signals which differ from those stimulated by the natural agonist through promoting an alternative agonist state of the receptor. This pathway selectivity combined with the receptor specificity of different substance-P analogues offers great potential for the tailored treatment of neuropeptide-dependent tumours.